Hubungan Dukungan Keluarga dan Depresi Dengan Kualitas Hidup pada Pasien dengan HIV/AIDS di Wonogiri, Jawa Tengah - Marni Marni; Nita Yunianti Ratnasari; Putri Halimu Husna; Domingos Soares (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
The number of people with HIV / AIDS in Indonesia is increasing from year to year, various problems that occur in patients with HIV / AIDS, namely physical, social and psychological problems. To overcome problems related to opportunistic infections, support antiretroviral therapy, prevent transmission of HIV / AIDS to others, motivate families to provide support and care for patients to be physically fit and not reportedly restore the patient's good quality of life. The purpose of this study was to analyze the relationship between family support and recovery with the quality of life of HIV / AIDS patients in the Gajah Mungkur Peer Support Group in Wonogiri, Central Java, Indonesia. The design of this research is quantitative research with cross sectional study. The population is HIV / AIDS patients who are members of the Gajah Mungkur Wonogiri Peer Support Group which is supported by around 130 people. The sampling technique with total sampling technique. Data collection tools are using a questionnaire, family support, Beck Depression Inventory (BDI), and WHOQOLHIV-BREF. Data were analyzed univariately, bivariate using the chi-square test, and multivariate analysis using multiple logistic regression tests. The p-value of the significance of the depression variable is 0.010 '